EPIDEMIOLOGICAL ANALYSIS OF THE PREVALENCE OF CHRONIC LIVER DISEASES AND MAJOR RISK FACTORS - Khadjayeva U. A.; Ibrohimov O. A. (Web of Journals Publishing, 2026)
Chronic liver diseases represent one of the most pressing problems of modern public health, with their global prevalence steadily increasing each year. This group of diseases includes chronic viral hepatitis, alcoholic and non-alcoholic fatty liver disease, autoimmune hepatitis, and liver cirrhosis. Worldwide, chronic liver diseases are among the leading causes of mortality and disability, placing a significant economic burden on healthcare systems. This literature review analyzes the epidemiological distribution, regional characteristics, and major risk factors influencing the development of chronic liver diseases based on scientific sources. The results indicate that unhealthy nutrition, viral infections, alcohol consumption, metabolic syndrome, and social-hygienic factors are the main determinants of chronic liver diseases.
Keywords: Chronic liver diseases, epidemiology, risk factors, viral hepatitis, fatty liver disease, liver cirrhosis, public health, prevention.